Investigation of genetic variation across the protein tyrosine phosphatase gene in patients with rheumatoid arthritis in the UK. Issue 5 (14th December 2006) - Hinks, Anne; Eyre, Steve; Barton, Anne; Thomson, Wendy; Worthington, Jane
Abstract : Objective: To investigate single-nucleotide polymorphisms (SNPs) across the PTPN22 gene region in a UK cohort of patients with rheumatoid arthritis (RA), to look for evidence of disease associations independent of the well-characterised R620W variant (rs2476601). Methods: 951 RA cases in the UK satisfying American Rheumatism Association (ARA) criteria and 448 population controls were genotyped for 11 SNPs across the PTPN22 gene region using the Sequenom MassArray MassEXTEND technology. Allele, genotype and estimated haplotype frequencies of cases and controls were compared. Results: In addition to the R620W (rs2476601) SNP, three SNPs were associated with RA in this study. The sole haplotype on which the associated T allele of R620W occurred was associated with RA; no other haplotypes showed a significant difference in frequencies between RA cases and controls. Conclusion: In contrast with a study of American patients with RA no evidence of association with PTPN22 independent of the well-characterised R620W variant was found, suggesting that in these patients this variant alone explains the association with the PTPN22 gene.